An optimized method for the extraction of ancient eukaryote DNA from marine sediments. (13th May 2020) - Armbrecht, Linda; Herrando‐Pérez, Salvador; Eisenhofer, Raphael; Hallegraeff, Gustaaf M.; Bolch, Christopher J. S.; Cooper, Alan
Abstract: Marine sedimentary ancient DNA ( sed aDNA) provides a powerful means to reconstruct marine palaeo‐communities across the food web. However, currently there are few optimized sed aDNA extraction protocols available to maximize the yield of small DNA fragments typical of ancient DNA (aDNA) across a broad diversity of eukaryotes. We compared seven combinations of sed aDNA extraction treatments and sequencing library preparations using marine sediments collected at a water depth of 104 m off Maria Island, Tasmania, in 2018. These seven methods contrasted frozen versus refrigerated sediment, bead‐beating induced cell lysis versus ethylenediaminetetraacetic acid (EDTA) incubation, DNA binding in silica spin columns versus in silica‐solution, diluted versus undiluted DNA in shotgun library preparations to test potential inhibition issues during amplification steps, and size‐selection of low molecular‐weight (LMW) DNA to increase the extraction efficiency of sed aDNA. Maximum efficiency was obtained from frozen sediments subjected to a combination of EDTA incubation and bead‐beating, DNA binding in silica‐solution, and undiluted DNA in shotgun libraries, across 45 marine eukaryotic taxa. We present an optimized extraction protocol integrating these steps, with an optional post‐library LMW size‐selection step to retain DNA fragments of ≤500 base pairs. We also describe a stringent bioinformatic filtering approach for metagenomic data and provide a comprehensive list of contaminants as a reference for future sed aDNA studies. The new extraction and data‐processing protocol should improve quantitative paleo‐monitoring of eukaryotes from marine sediments, as well as other studies relying on the detection of highly fragmented and degraded eukaryote DNA in sediments.